Current Landscape of Nutrition Within Prehabilitation Oncology Research: A Scoping Review - Gillis, Chelsia; Davies, Sarah J.; Carli, Francesco; Wischmeyer, Paul E.; Wootton, Stephen A.; Jackson, Alan A.; Riedel, Bernhard; Marino, Luise V.; Levett, Denny Z. H.; West, Malcolm A. (Frontiers in Nutrition, 2021)
Background: Prehabilitation aims to improve functional capacity prior to cancer treatment to achieve better psychosocial and clinical outcomes. Prehabilitation interventions vary considerably in design and delivery. In order to identify gaps in knowledge and facilitate the design of future studies, we undertook a scoping review of prehabilitation studies: to map the range of work on prehabilitation being carried out in any cancer type and with a particular focus on diet or nutrition interventions. Objectives: Firstly, to describe the type of prehabilitation programs currently being conducted. Secondly, to describe the extent to which prehabilitation studies involved aspects of nutrition, including assessment, interventions, implementation, and outcomes. Eligibility criteria: Any study of quantitative or qualitative design that employed a formal prehabilitation program before cancer treatment (“prehabilitation” listed in keywords, title, or abstract). Sources of evidence: Search was conducted in July 2020 using MEDLINE, PubMed, EMBASE, EMCARE, CINAHL, and AMED. Results: 550 unique articles were identified: 110 studies met inclusion criteria of a formal prehabilitation study in oncology. Prehabilitation studies were mostly cohort studies (41%) or randomized-controlled trials (38%) of multi-modal (49%) or exercise-only (44%) interventions that were applied before surgery (94%). Nutrition assessment was inconsistently applied across these studies, and often conducted without validated tools (48%). Of the 110 studies, 37 (34%) included a nutrition intervention component. Only half of these studies stated the goal for the nutrition component of their prehabilitation program; only 43% referenced accepted nutrition guidelines in surgery or oncology. Nutrition interventions largely consisted of counselling and dietary supplementation. The nutrition intervention was indiscernible in 24% of studies. Two-thirds of studies did not monitor the nutrition intervention nor evaluate nutrition outcomes. Conclusion: Prehabilitation literature lacks standardized and validated nutritional assessment, is frequently conducted without employing evidence-based nutrition interventions and is typically implemented without monitoring the nutrition intervention or evaluating the intervention’s contribution to outcomes. We suggest the development of a core outcome set would improve the quality of the studies, enable pooling of evidence and address some of the research gaps identified.